Serotypes With Low Invasive Potential Are Associated With an Impaired Antibody Response in Invasive Pneumococcal Disease - Littorin, Nils; Uddén, Fabian; Ahl, Jonas; Resman, Fredrik; Slotved, Hans-Christian; Athlin, Simon; Riesbeck, Kristian (Frontiers in Microbiology, 2018)
Pneumococcal polysaccharide vaccines may elicit a hyporesponse under certain conditions. There is limited knowledge, however, on the type of specific antibody response in individuals with invasive pneumococcal disease (IPD). The aim of this study was to investigate the functional antibody response in patients with IPD caused by different serotypes. Pre-immune and convalescent sera from 40 patients (age 14-91 years) with IPD caused by serotypes with low (serotype 3, 19F and 23F) and high (1, 4, 7F and 14) invasive potential were investigated. For each patient, the homologous serotype-specific antibody concentration was determined. The functionality of induced antibodies post-IPD was evaluated in an opsonophagocytic assay (OPA). Undetectable or decreased pneumococcal killing in OPA following IPD, i.e., a nonfunctional antibody response, was observed in 24 of 40 patients (60%). Patients with nonfunctional antibody responses had lower serotype specific IgG antibody ratios post-IPD than patients with increased OPA titres. A nonfunctional antibody response was associated with low invasive serotypes (3, 19F and 23F, p=0.015). In conclusion, a nonfunctional antibody response may follow IPD, and was in our cohort associated to serotypes with low invasive potential. These findings need to be confirmed in a larger material.